2008
DOI: 10.1590/s1807-59322008000400003
|View full text |Cite
|
Sign up to set email alerts
|

High Ratio of Triglycerides to HDL-Cholesterol Predicts Extensive Coronary Disease

Abstract: da Luz PL, Favarato D, Faria-Neto Jr JR, Lemos P; Chagas ACP. High ratio of triglycerides to HDL-cholesterol ratio predicts extensive coronary disease. Clinics. 2008;63:427-32. An abnormal ratio of triglycerides to HDL-cholesterol (TG/HDL-c) indicates an atherogenic lipid profile and a risk for the development of coronary disease. OBJECTIVE: To investigate the association between lipid levels, specifically TG/HDL-c, and the extent of coronary disease. METHODS: High-risk patients (n = 374) submitted for coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
106
1
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 271 publications
(129 citation statements)
references
References 21 publications
(18 reference statements)
5
106
1
6
Order By: Relevance
“…Corresponding lipid ratios of triglycerides/HDL cholesterol and triglycerides/non-HDL cholesterol were increasing with an increase in FR index. Overall, these findings were in agreement with other study of similar nature [8]. These findings validate the high risk profile for obstructive coronary artery disease in patients with abnormal lipid levels, which makes this population appropriate for the analysis of the correlation between lipid profile and extent of impairment of the coronary arteries.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Corresponding lipid ratios of triglycerides/HDL cholesterol and triglycerides/non-HDL cholesterol were increasing with an increase in FR index. Overall, these findings were in agreement with other study of similar nature [8]. These findings validate the high risk profile for obstructive coronary artery disease in patients with abnormal lipid levels, which makes this population appropriate for the analysis of the correlation between lipid profile and extent of impairment of the coronary arteries.…”
Section: Discussionsupporting
confidence: 91%
“…Several clinical and epidemiological studies have indicated a strong association between dyslipidemia and atherosclerosis [2]- [7]. Nevertheless, data on the association between lipid levels and extent or severity of coronary lesions in patients with coronary artery disease are limited [8]. Friesinger (FR) index [9] is an important tool to assess the extent and severity of coronary artery lesions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Luz et al found Friesinger index 0 in 19.0% patients, 1-4 in 17.9% patients, 5 -10 in 36.1% patients and 11-15 in 27.0% patients. 26 There was a strong positive correlation between the QTc dispersion and Leaman score (Pearson's correlation coefficient). Bampi et al observed that, Friesinger score 0-4 indicates less extensive disease and Friesinger score e"5 indicates extensive coronary atherosclerosis with extensive coronary artery disease.…”
Section: Discussionmentioning
confidence: 96%
“…[25][26][27] Female are less prone to developed IHD in premenopausal age due to protective role of estrogen, moreover smoking as a risk factor of IHD is less common in our country among female, which may explain male predominance of IHD. 28 The common risk factors for coronary artery disease in the present study showed that, smoking was the highest in Group-I followed by hypertension, family history of CAD, diabetes mellitus (DM) and dyslipidemia.…”
Section: Prolonged Qtc Dispersion and Leaman Scorementioning
confidence: 99%